An attempt to evaluate the acceptance of homosexuality in Polish society - Mazurkiewicz, Dariusz Wojciech; Marek, Alina; Miela, Robert Joseph; Wójcik, Halina (Polish Journal of Public Health, 2013)
Homosexuality has always been considered an embarrassing subject by most Judaic, Christian and Islamic societies, a phenomenon contrary to the accepted social norms and the teachings of the Church and especially contrary to the Catholic Church doctrines. Only in 1975, The American Psychiatric Association eliminated homosexuality from the DSM classification, as not being a mental disorder. Sixteen years later World Health Organisation did the same by removing the terms regarding homosexuality from the ICD.In 1976, the government of the Federal Republic of Germany lifted the ban of homosexual contacts for people under 21 years of age a year later, while the government of Great Britain passed a legislation abolishing the differentiation of the legal age of initiation for homosexuals. In 1981, discrimination for sexual orientation was banned in Norway by an appropriate legislation.It is unquestionable that a punishment for homosexual acts would still be inflicted in 50% of the states in the United States of America in 1993.It has been established that the evaluation of the distribution of sexual identity in the society (including homosexual ones) is extremely difficult which may be proven by the fact that “in the legal and canonical rulings, homosexuality is one of the most commonly occurring psychosexual disorder”. The issue regarding the role of a parent in the problem of homosexual identity gives rise to social controversies.It should be taken for granted that currently, Polish society is not prepared to approve homosexuality in all areas of social and family life to be on a par with the formal or informal heretosexual relationships and all their “entitelements”.